Positive‐Feedback Regulation of Subchondral H‐Type Vessel Formation by Chondrocyte Promotes Osteoarthritis Development in Mice. (24th March 2018) - Lu, Jiansen; Zhang, Haiyan; Cai, Daozhang; Zeng, Chun; Lai, Pinglin; Shao, Yan; Fang, Hang; Li, Delong; Ouyang, Jiayao; Zhao, Chang; Xie, Denghui; Huang, Bin; et al.
ABSTRACT: Vascular‐invasion‐mediated interactions between activated articular chondrocytes and subchondral bone are essential for osteoarthritis (OA) development. Here, we determined the role of nutrient sensing mechanistic target of rapamycin complex 1 (mTORC1) signaling in the crosstalk across the bone cartilage interface and its regulatory mechanisms. Then mice with chondrocyte‐specific mTORC1 activation ( Tsc1 CKO and Tsc1 CKO ER ) or inhibition ( Raptor CKO ER ) and their littermate controls were subjected to OA induced by destabilization of the medial meniscus (DMM) or not. DMM or Tsc1 CKO mice were treated with bevacizumab, a vascular endothelial growth factor (VEGF)‐A antibody that blocks angiogenesis. Articular cartilage degeneration was evaluated using the Osteoarthritis Research Society International score. Immunostaining and Western blotting were conducted to detect H‐type vessels and protein levels in mice. Primary chondrocytes from mutant mice and ADTC5 cells were treated with interleukin‐1β to investigate the role of chondrocyte mTORC1 in VEGF‐A secretion and in vitro vascular formation. Clearly, H‐type vessels were increased in subchondral bone in DMM‐induced OA and aged mice. Cartilage mTORC1 activation stimulated VEGF‐A production in articular chondrocyte and H‐type vessel formation in subchondral bone. Chondrocyte mTORC1 promoted OA partially through formation of VEGF‐A–stimulated subchondral H‐type vessels. In particular, vascular‐derived nutrients activated chondrocyte mTORC1, and stimulated chondrocyte activation and production of VEGF, resulting in further angiogenesis in subchondral bone. Thus a positive‐feedback regulation of H‐type vessel formation in subchondral bone by articular chondrocyte nutrient‐sensing mTORC1 signaling is essential for the pathogenesis and progression of OA. © 2018 American Society for Bone and Mineral Research